2004
DOI: 10.1271/bbb.68.286
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Thermophilic Ammonium-tolerant Bacterium and Its Application to Reduce Ammonia Emission during Composting of Animal Wastes

Abstract: A thermophilic bacterium, strain TAT105, was isolated from compost made of animal wastes. TAT105 had high tolerance to ammonium nitrogen up to 1200 mM, and highly assimilated nitrogen during the growth on swine feces. The strain was classified into Bacillus, close to Bacillus pallidus. To evaluate the effect of adding TAT105 to ammonia (NH3) emission during the composting process of animal wastes, laboratory scale composting was done. NH3 emission tended to be lower and nitrogen loss was smaller in the TAT105-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 1 publication
2
42
0
Order By: Relevance
“…In our previous study, composting was performed for 18 days to evaluate the effect of TAT105 using the present system, 22) and it was confirmed that 70-80% of the TN loss as NH 3 gas from the composted material occurred within the first seven days of composting in this system. After the first seven days, the difference in nitrogen loss between the treatments with and without TAT105 showed little difference.…”
Section: Composting Testssupporting
confidence: 68%
See 4 more Smart Citations
“…In our previous study, composting was performed for 18 days to evaluate the effect of TAT105 using the present system, 22) and it was confirmed that 70-80% of the TN loss as NH 3 gas from the composted material occurred within the first seven days of composting in this system. After the first seven days, the difference in nitrogen loss between the treatments with and without TAT105 showed little difference.…”
Section: Composting Testssupporting
confidence: 68%
“…22) A solid medium for the TAT105 additive was prepared as follows: 375 g of wheat bran, 125 g of coaled pulp sludge (Cellash, Nippon Kakoh Seishi Co., Ltd., Takahagi), and 7.5 g of soluble starch were mixed with a solution containing 1.5 g of yeast extract (Difco), 0.5 g of Na 2 HPO 4 , 0.67 g of NH 4 Cl, and 0.5 mL of a 10 mM MnCl 2 ·4H 2 O solution in 500 mL of distilled water. Portions (250 g) of the medium were placed in several 2-L Erlenmeyer flasks capped with cotton plugs and autoclaved at 121°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations